KEMALANGAN MAUT JALAN RAYA MENURUT PERSPEKTIF UNDANG-UNDANG MALAYSIA DAN ISLAM - Ismail, Siti Zubaidah (Jurnal Syariah, 2019)
The issue of traffic accident has created a stir among the public lately due to increasing numbers of fatal accident in recent years. Many cases have been brought to court and the culprits have been punished according to the law. Some parties express their dissatisfaction regarding punishment claiming that the offender deserve more than what they were convicted (and punished) with. In the first section of the article, the writer highlights the provisions under the Road Transportation Act J987 and the related proviso in the Penal Code regarding the issue. In the second section, she discusses Muslim jurists ' opinion about the issue of traffic accident, and finds that their discussion merely focuses on the aspect of injury (and compensation) caused by animals - a mode of transportation during their era - which are quite irrelevant in the modern world. She emphasises that, since the present sophisticated means of transportation were nol available during that era, an analogy is needed to elaborate the various aspects of accident as a result of high-tech "lifeless" vehicles and the related issue of homicide.